'A New Career': nostalgia, mortality, and David Bowie's 'I Can't Give Everything Away'. Issue 4 (2nd October 2021) - Masterson, Alice
ABSTRACT: David Bowie's swansong album Blackstar occupies a unique position in its proximity to the artist's death: just two days. It thus provides an opportunity to examine how music, nostalgia, and mortality interact. Combining study into the links between music and nostalgia and analysis of use of quotation, I propose a reading of a 'dual effect' in which the track 'I Can't Give Everything Away' explores themes of nostalgia and mortality whilst encouraging nostalgic feeling in its audiences. The article contributes to an understanding of how a musician's death can alter audience interaction with their music, and how music itself can reflect mortality.